2015
DOI: 10.3389/fnagi.2015.00124
|View full text |Cite
|
Sign up to set email alerts
|

Microglial cell dysregulation in brain aging and neurodegeneration

Abstract: Aging is the main risk factor for neurodegenerative diseases. In aging, microglia undergoes phenotypic changes compatible with their activation. Glial activation can lead to neuroinflammation, which is increasingly accepted as part of the pathogenesis of neurodegenerative diseases, including Alzheimer’s disease (AD). We hypothesize that in aging, aberrant microglia activation leads to a deleterious environment and neurodegeneration. In aged mice, microglia exhibit an increased expression of cytokines and an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
358
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(376 citation statements)
references
References 292 publications
(375 reference statements)
12
358
0
6
Order By: Relevance
“…This may be a greater concern as individuals age because the aging process influences the activity of these glial cells in a manner that further shifts microglia towards the 'primed' phenotype, which we hypothesize decreases the brain's resilience 173 . This hypothesis is similar to that of other research groups who have postulated that TBI is lowering the brain's resilience (or 'cognitive reserve') through these microglial-mediated mechanisms 53,54,168,174 .…”
Section: Potential Clinical Implicationsmentioning
confidence: 91%
“…This may be a greater concern as individuals age because the aging process influences the activity of these glial cells in a manner that further shifts microglia towards the 'primed' phenotype, which we hypothesize decreases the brain's resilience 173 . This hypothesis is similar to that of other research groups who have postulated that TBI is lowering the brain's resilience (or 'cognitive reserve') through these microglial-mediated mechanisms 53,54,168,174 .…”
Section: Potential Clinical Implicationsmentioning
confidence: 91%
“…Recent microarray analysis of human brain tissue has demonstrated a significant age-related upregulation of genes associated with inflammation and immune system activation (Cribbs et al, 2012;Mohan et al, 2016;Nikas, 2013). In animal models of aging, studies have reported an exaggerated response (production of pro-inflammatory cytokines; microglial activation) following treatment with the bacterial endotoxin lipopolysaccharide (LPS) (Matt and Johnson, 2016;von Bernhardi et al, 2015). While LPS-induced neuroinflammation is a far from perfect model of the inflamed aging brain, it does demonstrate the differential response of young and aged neuroimmune cells to an inflammatory stimulus.…”
Section: Adult Hippocampal Neurogenesis and Inflammationmentioning
confidence: 99%
“…De fet, es reconeix àmpliament que aquests trastorns sense una preponderància genètica són multifactorials i associats tant amb el seu genoma com amb les condicions ambientals. Encara que les molècules i les vies de senyalització involucrades en la resposta inflamatòria han estat àmpliament caracteritzades, encara no està clar com influeixen en el desenvolupament de malalties neurodegeneratives i la vinculació que tenen amb les condicions mediambientals (Bernhardi, 2015). Aquesta reacció neuroinflamatòria no només englobaria l'activació de cèl·lules glials, sinó també la infiltració de cèl·lules perifèriques del sistema immune (Schwartz, 2013).…”
Section: Les Malalties Neurodegeneratives I La Neuroinflamacióunclassified